Desain Pembelajaran Berbasis Case Study pada Mata Kuliah Pendidikan IPS - Piki S Pernantah; Khairiyah Khadijah; Mirza Hardian; Bedriati Ibrahim; Masro F Khasanah (Indonesian Journal of Social Science Education (IJSSE), 2022)
The Social Studies Education course is expected to contribute to fostering student national awareness, social insight, social spirit, and social sensitivity to foster good social interaction in social life. In the learning process, social studies education courses must prioritize active learning. The case study learning method can make students better understand the material and master more contextual learning in accordance with the semester learning design that has been prepared. This article aims to: 1) describe the importance of case study-based social studies courses with learning innovations finding advantages, such as: a. students can be the main focus (student oriented) who strive to solve cases given during lectures; b. students can actively analyze and discuss cases given by lecturers to find solutions (problem solving).; 2) designing learning scenarios with the case study method in the Social Studies Education course. This research resulted in a case study-based learning design consisting of five steps in the Social Studies Education course